The Importance of Health and Safety at African Mine Sites - Bocoum, Brigitte (World Bank, Washington, DC, 2017)
This knowledge note promots the equity and shared prosperity calls for a closer look at the working and living conditions of millions of mine workers in Africa, where tuberculosis (TB) imposes a high burden on mining economies and constitutes a regional public health crisis. Health hazards are perpetuated by poor enforcement of mining legislation, limited application of best international practices, weak institutions, and inadequate equipment and skills. Attention by Africa’s regional economic communities and the international donor community is needed. In uncontrolled mining operations and communities of the type common in Africa, several factors combine to form a perfect storm for TB infection and transmission. The practice of allowingmining companies to self-report on health issues should be eliminated. Legislation on the healthaspects of mining operations in Africa must be developed in line with international standards andbest practices. The continent’s regional development communities should act urgently to establish public-private partnerships capable of ensuring that mining in fact benefits the region’speople in their path toward sustainable development. The goal should be the adoption ofpreventive measures to avoid further damage to the region’s health and skilled human capital. The necessary partnerships will have to engage the major players on the African mining scene in cooperation toward common objectives.